UPAYA MENINGKATKAN KESADARAN PUBLIK MELALUI DIFFUSI PROMOSI CERUTU JEMBER DI PT TARUTAMA NUSANTARA - Resvindira Damayanti (MEDIAKOM, 2023)
This research aims to identify and analyze the efforts made to increase public awareness through the diffusion of Jember cigar promotion at PT Tarutama Nusantara. With increasing competition in the cigar market, it is important to understand how promotions can be an effective tool in increasing public awareness of cigars in Jember Regency. The rationale for this research is based on the diffusion of innovation theory and marketing communication theory, which emphasizes the importance of effective communication in influencing consumer perceptions and behavior. The methodology used is a qualitative approach, by collecting data through in-depth interviews with subman related to the promotion of Jember cigars at PT Tarutama Nusantara and the general public regarding the existence of cigars. Research findings show that PT Tarutama Nusantara has used various promotional strategies, including advertising, event sponsorship, and sales promotions to increase public awareness of cigars. However, there are still challenges in promotional effectiveness, such as consumer preferences or choices, price and lack of adequate mass media exposure. Therefore, this research provides recommendations for improving internal coordination and market research regarding public awareness regarding the existence and superiority of cigars in Jember Regency. It is hoped that the results of this research can provide valuable insight for PT Tarutama Nusantara and other companies in the cigar industry to increase public awareness and optimize their promotional strategies. Keyword: Jember Cigars; Promotion; Tarutama Nusantara